IMPLEMENTING GOOD GOVERNANCE THROUGH DIGITAL BASED PUBLIC SERVICE DELIVERY IN BARRU REGENCY GOVERNMENT: AN NVIVO ANALYSIS - Aidah. S; Marsuki (P3M Stia Al Gazali Barru and Meraja media, 2026)
[Full Paper] to pdf Copyright (c) 2026 Meraja journal